Pelatihan dan Pendampingan Penulisan Karya Tulis Ilmiah Bagi Guru SD - Ilfiandra Ilfiandra; Uman Suherman; Sudaryat Nurdin Akhmad; Amin Budiamin; Setiawati Setiawati (Jurnal Pengabdian Pada Masyarakat, 2016)
The main goal of this program is supplying elementary school teachers who have competence in writing paper on developing teacher profession. Operationally, the goals of program are: 1) supplying skilled teachers who are ready to do socialization many kinds of developing of teacher profession; 2) helping teacher to be able to develop their profession especially in writing scientific paper of result of classroom action research (PTK); 3) skilling teachers in conducting classroom action research in their classroom; 4) skilling teachers in arranging report of research and scientific journal article of PTK result, and 6) publishing special edition journal that contained the article of PTK result that written by teachers. For pursuit the goals, here it is using methods of training, workshop ad assistance. In the end of this program, the gained result are: 1) there are 27 elementary teachers class of IVa participating the training program wholly in 26 hours of lesson; 2) 4 times of assistance program have been conducted in several activities of planning, actuating, and writing report of PTK; 3) 27 report of PTK are supplied by every participants by guiding and directing of assistance team; 4) 27 articles of PTK result are supplied that is possibly published in local journal or national; 5) a publisher is built in local of “MANONJAYA” for promoting result of teacher PTK; and 6) the best two articles are ready to be published by publisher in UPI.